Liyongo Songs. Poems attributed to Fumo Liyongo. - Drolc, Ursula (Afrikanistik online, 2006)
The edition is an excellent prove of a possible and successful cooperation of various leading scholars in Swahili linguistics, literature, and poetry with local experts on Swahili tradition. The Liyongo Working Group consists of Bi. Zeina Mahmoud Fadhil Al-Bakary (London), Sheikh Yahya Ali Omar (London), Sheikh Ahmed Nabahany (Mombasa), Mohamed H. Abdulaziz (Nairobi), Sheikh Ahmad Nassir Juma Bhalo (Mombasa), Farouk Topan (London), Angelica Baschiera (London), Abdilatif Abdalla (Leipzig), Gudrun Miehe (Bayreuth), Said Khamis (Bayreuth), Clarissa Dittemer (Bayreuth). The Liyongo Working Group has achieved the great and difficult task to preserve a very important piece of Swahili cultural heritage and make it accessible.
Keywords: Liyongo; Poetry; Swahili